Gestão da inovação e as particularidades da atividade de desenvolvimento de software: o caso da região da Grande Vitória/ES - Dias, Dnilson Carlos; Pinto, Miriam de Magdala (Revista Gestão da Produção Operações e Sistemas, 2006)
The technology management processes, mainly the innovative ones, are complex, involving a number of actors and institutions. This paper presents the problems related to the institutional issues in the software area and their influences on the management model development for said economic activity. Such discussion relates the theoretical issues presented with the case study on the software business in the metropolitan region in the city of Vitória, Brazil. Based on the New Institutional Economy reasoning and the neo-Schumpeterian theory, this paper shows that the development of this business is extremely uncertain and highly related to local issues. Keywords: Innovation management; Software development; New institutionalist economics; Neo- Schumpeterian economics.